CONNECTIVE TISSUE DISEASE ASSOCIATED INTERSTITIAL LUNG DISEASE - AN ACUTE EXACERBATION IN EMERGENCY ROOM - Shahzad, Tahir (Journal of Ayub Medical College Abbottabad, 2018)
Interstitial lung disease (ILD) is a pathology involving lower respiratory tract, causing damage to the alveolar walls and vascular bed, resulting in decreasing functional alveolar units. Two third cases of ILD are idiopathic and one third cases of ILD are related to connective tissue disease (CTD). Clinical course of ILD is chronic and progressive in nature, CTD-ILD has a better prognosis compared to idiopathic ILD. Acute exacerbations are life-threatening and require close monitoring and immediate treatment, though CTD-ILD initial clinical manifestation at first clinical encounter is rarely found to be life threatening or acute exacerbation of ILD. I am reporting a case of CTD-ILD presenting to the Emergency Room of Memon Medical Institute Hospital (MMIH) manifesting as acute exacerbation of underlying ILD. Keywords: Acute exacerbation; Interstitial lung disease; CTD-ILD; Connective tissue disease